Design and Analysis of Trash Monitoring System Prototype Based On Internet of Things (IoT) Using MQTT Protocol - Achmad Auliyaa Zulfikri; Doan Perdana; Gustommy Bisono (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
On this research, Internet of Things (IoT) as an advanced technology is used to monitor the height of trash from a trash can in order to give notification whether the height of trash is already reaching the maximum height limit or not. To support those needs, we used NodeMCU as a microcontroller, ultrasonic sensor, MQTT as IoT protocol, and Android to display the data. After we did the system performance test, we had the biggest result of end-to-end delay which was 2.06875 seconds when the packet delivery was set to 1000 ms with 3 active nodes and the smallest result of end-to-end delay which was 0.26055 seconds when the packet delivery was set to 100 ms with 1 active node. The biggest result of throughput was 597.17 Bytes/s when the packet delivery was set to 100 ms with 1 active node and the smallest result of throughput was 75.86 Bytes/s when the packet delivery was set to 1000 ms with 3 active nodes. The biggest result of availability and reliability was 99.905% when the packet delivery was set to 1000 ms and the smallest result was 99.833% when the packet delivery was set to 100 ms.